46.2k views
3 votes
Solve equation 9(3x+7)-3.5 = -8

2 Answers

7 votes

Explanation:

Hey there!

Given;


9(3x + 7) - 3.5 = - 8

Perform the operations in left side.


27x + 63 - 3.5 = - 8

Simplify the like terms and find value of x.


27x + 59.5 = - 8


27x = - 8 - 59.5


27x = - 67.5


x = ( - 67.5)/(27)

Therefore the value of x is "-2.5".

Check;

9(3×-2.5+7) - 3.5 = -8

-4.5 - 3.5 = -8

-8 = -8 (True).

Hope it helps...

User Trevor Rowe
by
5.4k points
5 votes

Answer: " x = - 2.5 " .

___________________________________________

Step-by-step explanation:

Given:

9(3x + 7) - 3.5 = - 8 ; Solve for "x" ;

First: Let us add "3.5" ; to both sides of the equation:

9(3x + 7) - 3.5 = - 8 ;

+ 3.5 = + 3.5 ;

___________________________________________

to get:

9(3x + 7) = - 4.5 ; [Note that " -3.5 + 3.5 = 0" ; [Cancels out to "0".].

Second: Let us expand the expression on the "left-hand side" of the equation.

" 9(3x + 7) " ;

Note the "distributive property" of multiplication:

" a(b + c) = ab + ac " ;

As such:

9(3x + 7) = 9(3x) + 9(7) = 27x + 63 ;

Third:

Now, replace this term for the original expression, on the "left-hand side" of the equation; & Rewrite the equation:

27x + 63 = - 4.5 ;

Fourth: Now, we can divide each side of the equation by "9" ;

(27x + 63) / 9 = (-4.5)/9 ;

to get:

(27x/9) + (63/9) = (-4.5/9) ;

to get:

3x + 7 = -0.5 ;

Fifth:

Subtract "7" ; from Each side of the equation:

3x + 7 = -0.5 ;

- 7 = - 7 ;

___________________________________________

to get:

3x = -7.5 ; [Note that " +7 - 7 = 0" ; [Cancels out to "0".] ;

___________________________________________

Sixth: Divide each side of the equation by "3";

to isolate "x" on one side of the equation; & to solve for "x" ;

___________________________________________

3x / 3 = -7.5 / 3 ;

to get:

x = - 2.5 .

___________________________________________

Hope this helps!

Best wishes!

___________________________________________

User LdM
by
5.5k points